2008
DOI: 10.1007/s10493-008-9149-7
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of phytophagous and predaceous mites on coffee in Brazil, with emphasis on Brevipalpus phoenicis (Acari: Tenuipalpidae)

Abstract: The objective of this work was to study the population dynamics of Brevipalpus phoenicis (Geijskes) and predaceous mites (Phytoseiidae and Stigmaeidae), as well as the interactions among these mite species, in a coffee plantation in the State of São Paulo, Brazil. Tydeids were also evaluated because of the high frequency of these mites on coffee plants. Samples of leaves, branches and fruits were taken fortnightly, from April 2001 to June 2003, from plants randomly chosen in the coffee plantation. B. phoenicis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 34 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…Colonies of O. ilicis are found on the upper leaf surface; leaves may drop prematurely as a consequence of high infestations. The false spider mite B. phoenicis is found on both leaf surfaces at low population levels (Flechtmann 1983;Mineiro et al 2008) and may transmit coVee ringspot virus (Kitajima et al 2003, Mineiro et al 2008. The phytoseiid mite I. zuluagai is an important predator commonly associated with phytophagous mites in coVee plantations in Brazil (Pallini Filho et al 1992;Reis et al 2000).…”
Section: Mite Rearingmentioning
confidence: 99%
“…Colonies of O. ilicis are found on the upper leaf surface; leaves may drop prematurely as a consequence of high infestations. The false spider mite B. phoenicis is found on both leaf surfaces at low population levels (Flechtmann 1983;Mineiro et al 2008) and may transmit coVee ringspot virus (Kitajima et al 2003, Mineiro et al 2008. The phytoseiid mite I. zuluagai is an important predator commonly associated with phytophagous mites in coVee plantations in Brazil (Pallini Filho et al 1992;Reis et al 2000).…”
Section: Mite Rearingmentioning
confidence: 99%
“…The mites collected from the coffee plants belonged to the families Phytoseiidae, Stigmaeidae and Cunaxidae, and these are commonly found in leaf domatia all over the world. These are all predatory mites and mites from these families have previously been shown to be associated with coffee plantations [3,12]. Matos et al [19] found that coffee domatia had a positive effect on the abundance of predatory mites, and plants with higher densities of domatia harbour more predatory mites and fewer prey mites.…”
Section: Discussionmentioning
confidence: 96%
“…The mutualism with mites is important in coffee because it may provide some relief from one of the most important diseases of coffee plants, the coffee leaf rust fungus (Hemilleia vastatrix Berk and Boome), and also from phytophagous mites [8]. In Brazil, the top coffee-producing country in the world, these benefits are appreciated, and more studies are being undertaken in an attempt to understand the possible interactions among the different mite species found in coffee and the favourable environmental conditions for the predaceous mites on coffee plants, in order to improve their integrated pest management programs for coffee agroforest systems [12]. Furthermore, coffee plants may also benefit from an increased overall fitness due to a decrease in the damage caused by plant enemies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations